KELAYAKAN FINANSIAL PRODUKSI PEKTIN DARI KULIT PISANG DI UD. BURNO SARI, SENDURO - KAB. LUMAJANG - Nurhayati Nurhayati; Nita Kuswardhani; Dwika Mayang Sari (Faculty of Agricultural Technology, University of Jember, 2015)
Banana is a tropical fruit which is the most widely produced and used by the community of Indonesia. banana Production have first ranked crops in Indonesia. Banana contain pectin with high concentrations. The content of pectin in banana peel ranged from 1.92 to 3.25% of the dry weight. The purpose of this study were to determine a pectin yield, knowing the factors that affect the quality of pectin, analyzes of Financial Feasibility of Pectin Production from Banana peel in UD. Burno Sari. The result of pectin from banana peel was conducted a pectin yield calculation, the study of fishbone diagrams, and tested of financial feasibility. Research results of pectin production from banana peel showed the yield generated from waste banana skin by using a temperature of 80 ° C and the method used was the extraction of 2 levels of 8,78%, the study results of fishbone diagram showed some of the causes that are considered to be factors that affected the quality of product. Human resources, raw materials and production process was considered to be an important factor determining the quality of the products, on human resources factors allegedly contained 2 causees were lack of oversight and labor have not been trained, the factors of raw materials allegedly due to the maturity level of banana peel which used, then the factor of the production process because of two causes, namely the drying of raw materials and the process of downsizing. Results of the test showed business financial feasibility of pectin production from banana peels was feasible with NPV: Rp 19.573.074, B/C Ratio: 1,03, PBP: 3,24 Years, BEP Units: 61 units / year, BEP Rp : USD 32.983.672 / year, IRR: 24,72%.Keywords: banana peel, extraction of pectin, financial feasibility